Marketing of the online communities - Pražan, Jan; Karlíček, Miroslav, 1979-; Řídel, Jakub; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2011)
The Bachelor Thesis "Marketing of the online communities" is devoted to online virtual communities, one of the phenomena of the current Internet. Goal of this thesis is to determine the factors that predispose the successful operation of online communities. The thesis defines the essentials features of social media, characterized by online communities and their role in marketing. It deals with strategic and tactical aspects of building and maintaining successful online communities. Based on the analysis of five selected Czech successful media (online communities) from different areas determine the factors, that predispose the successful operation of online communities. The work provides guidance for companies and individuals to build and maintain their own viable online community so that it leads to meet its marketing objectives.
Vedoucí práce: Miroslav Karlíček
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor bakal. práce]; bakalářské práce; bachelor's theses